AAPH-induced oxidative damage reduced anion exchanger 1 (SLC4A1/AE1) activity in human red blood cells: protective effect of an anthocyanin-rich extract - Remigante, Alessia; Spinelli, Sara; Patanè, Giuseppe Tancredi; Barreca, Davide; Straface, Elisabetta; Gambardella, Lucrezia; Bozzuto, Giuseppina; Caruso, Daniele; Falliti, Giuseppe; Dossena, Silvia; Marino, Angela; Morabito, Rossana (Frontiers in Physiology, 2023)
During their lifespan in the bloodstream, red blood cells (RBCs) are exposed to multiple stressors, including increased oxidative stress, which can affect their morphology and function, thereby contributing to disease. Aim: This investigation aimed to explore the cellular and molecular mechanisms related to oxidative stress underlying anion exchanger 1 activity (band 3, SLC4A1/AE1) in human RBCs. To achieve this aim, the relationship between RBC morphology and functional and metabolic activity has been explored. Moreover, the potential protective effect of an anthocyanin-enriched fraction extracted from Callistemon citrinus flowers was studied. Methods: Cellular morphology, parameters of oxidative stress, as well as the anion exchange capability of band 3 have been analyzed in RBCs treated for 1 hour with 50 mM of the pro-oxidant 2,2′-azobis (2-methylpropionamide)-dihydrochloride (AAPH). Before or after the oxidative insult, subsets of cells were exposed to 0.01 μg/mL of an anthocyanin-enriched fraction for 1 hour. Results: Exposure to AAPH caused oxidative stress, exhaustion of reduced glutathione, and over-activation of the endogenous antioxidant machinery, resulting in morphological alterations of RBCs, specifically the formation of acanthocytes, increased lipid peroxidation and oxidation of proteins, as well as abnormal distribution and hyper-phosphorylation of band 3. Expected, oxidative stress was also associated with a decreased band 3 ion transport activity and an increase of oxidized haemoglobin, which led to abnormal clustering of band 3. Exposure of cells to the anthocyanin-enriched fraction prior to, but not after, oxidative stress efficiently counteracted oxidative stress-related alterations. Importantly, protection of band3 function from oxidative stress could only be achieved in intact cells and not in RBC ghosts. Conclusions: These findings contribute a) to clarify oxidative stress-related physiological and biochemical alterations in human RBCs, b) propose anthocyanins as natural antioxidants to neutralize oxidative stress-related modifications, and 3) suggest that cell integrity, and therefore a cytosolic component, is required to reverse oxidative stress-related pathophysiological derangements in human mature RBCs.